Mpox in the New York metropolitan area, Summer 2022. Issue 4 (1st April 2023) - Gnanaprakasam, Rachel; Keller, Marina; Glassman, Rebecca; El‐Khoury, Marc Y.; Chen, Donald S.; Feola, Nicholas; Feldman, Jared; Chaturvedi, Vishnu
Abstract: Early in the 2022 Mpox (MPX) global outbreak, caseloads in the New York Metropolitan area climbed rapidly before other US urban areas. This case series summarizes the authors' clinical experience detecting and treating MPX, during a quickly evolving outbreak. Clinical outcomes were recorded with a focus on varied clinical presentation and outcomes such as complications and response to experimental tecovirimat therapy. A focal or multifocal rash was the most common presenting symptom in 91% of patients. Almost two‐thirds (62%) of patients had anogenital involvement. Proctitis was one of the most painful presentations with 75% requiring antiviral treatment and three patients needing hospitalization for pain management. Most patients responded promptly to antiviral treatment with tecovirimat. Five out of 10 patients treated with tecovirimat reported symptom resolution within 48–72 h of therapy and another three saw resolution within first 96 h. Two patients had poor response to tecovirimat. This series includes the only reported case of an HIV positive, immunocompetent patient who experienced recurrent anal ulcers due to Mpox and required a second course of tecovirimat. Other unique presentations included urethritis, abscess formation and MPX infection postvaccination. Control of this current Mpox outbreak was possible due to timely diagnosis and the availability of both a licensed vaccine and an investigational drug.